Antimicrobial Wound Dressing Containing Silver Sulfadiazine With High Biocompatibility: In Vitro Study. Issue 8 (20th April 2016) - Mohseni, Mina; Shamloo, Amir; Aghababaei, Zahra; Vossoughi, Manouchehr; Moravvej, Hamideh
Abstract: Many patients all over the world suffer from acute wounds caused by traumas or burns. In most crucial cases, skin regeneration cannot be promoted spontaneously, and skin grafts are applied as the main treatment. However, this therapy has some drawbacks which motivate researchers to develop wound dressings. In this study, electrospun mats consisting of polycaprolactone (PCL) and polyvinyl alcohol (PVA) incorporated with silver sulfadiazine (SSD) are proposed to be used as antimicrobial wound dressings with the capability of cell seeding. Various amounts of SSD were loaded into PVA nanofibers, and the effects of SSD particles on the morphological characteristics of nanofibers, mechanical behaviors, and physical properties of the mats were studied for the first time. The cellular viability, antimicrobial properties of the scaffolds, and release behavior of silver were also examined. Finally, the best concentration of SSD was determined based on the quality of nanofibers, antibacterial features, and the ability of cellular attachment and proliferation. Fibronectin was also coated to enhance the biocompatibility of the selective scaffold. It was shown that the mats have appropriate mechanical properties with good handling ability in wet environment and also have a hydrophilic surface to adhere to the wound bed. Results indicate that SSD particles increase the fiber diameter and hydrophilic properties, while they weaken the mechanical characteristics of the mats. Furthermore, 5 wt% SSD/PVA was determined as the best concentration of SSD as it results in a desirable fiber quality for the mats with enough antimicrobial properties and acceptable cell proliferation on the surface. Coating fibronectin was also introduced as an effective method to increase the biocompatibility of the scaffolds incorporated with SSD particles.